Whole genome duplication of wild-type and CINNAMYL ALCOHOL DEHYDROGENASE1-downregulated hybrid poplar reduces biomass yield and causes a brittle apex phenotype in field-grown wild types - Wouters, Marlies; Corneillie, Sander; Dewitte, Angelo; Van Doorsselaere, Jan; Van den Bulcke, Jan; Van Acker, Joris; Vanholme, Bartel; Boerjan, Wout (Frontiers in Plant Science, 2022)
The potential of whole genome duplication to increase plant biomass yield is well-known. In Arabidopsis tetraploids, an increase in biomass yield was accompanied by a reduction in lignin content and, as a result, a higher saccharification efficiency was achieved compared with diploid controls. Here, we evaluated whether the results obtained in Arabidopsis could be translated into poplar and whether the enhanced saccharification yield upon alkaline pretreatment of hairpin-downregulated CINNAMYL ALCOHOL DEHYDROGENASE1 (hpCAD) transgenic poplar could be further improved upon a whole genome duplication. Using a colchicine treatment, wild-type (WT) Populus tremula x P. alba cv. INRA 717-1B4, a commonly used model clone in tree biotechnology research, and hpCAD tetraploids were generated and grown in the greenhouse. In parallel, WT tetraploid poplars were grown in the field. In contrast to Arabidopsis, a whole genome duplication of poplar had a negative impact on the biomass yield of both greenhouse- and field-grown trees. Strikingly, field-grown WT tetraploids developed a brittle apex phenotype, i.e. their tip broke off just below the apex. In addition, the chromosome doubling altered the biomass composition of field-grown, but not of greenhouse-grown tetraploid poplars. More specifically, the lignin content of field-grown tetraploid poplars was increased at the expense of matrix polysaccharides. This increase in lignin deposition in biomass is likely the cause of the observed brittle apex phenotype, though no major differences in stem anatomy or in mechanical properties could be found between di- and tetraploid WT poplars grown in the field. Finally, the saccharification efficiency of greenhouse- and field-grown WT and greenhouse-grown hpCAD diploids was maintained in tetraploids. This study showed that a whole genome duplication in hybrid WT and hpCAD poplar did neither result in further improvements in biomass yield, nor in improved biomass composition and, hence, saccharification performance.